Plant virus ecology and epidemiology: historical perspectives, recent progress and future prospects - Jones, R.A.C (Annals of applied biology, 2014)
After clarifying the relationship between the closely related concepts of ecology and epidemiology as they are used in plant virology, this article provides a historical perspective on the subject before discussing recent progress and future prospects. Ecology focuses on virus populations interacting with host populations within a variable environment, while epidemiology focuses on the complex association between virus and host plant, and factors that influence spread. The evolution and growth of plant virus ecology and epidemiology since its inception to the present day, and the major milestones in its development, are illustrated by examples from influential historical reviews published in the Annals of Applied Biology over the last 100 years. Original research papers published in the journal are used to illustrate important ecological and epidemiological principles and new developments in both fields. Both areas are multifaceted with many factors influencing host plants, and virus and vector behaviour. The highly diverse scenarios that arise from this process influence the virus population and the spatiotemporal dynamics of virus distribution and spread. The review then describes exciting progress in research in the areas of molecular epidemiology and ecology, and understanding virus–vector interactions. Application of new molecular techniques has greatly accelerated the rate of progress in understanding virus populations and the way changes in these populations influence epidemics. Viruses cause direct and plant‐mediated indirect effects on insect vectors by modifying their life cycles, fitness and behaviour, and one of the most fascinating recent fields of research concerns plant‐mediated indirect virus manipulation of insect vector behaviour that encourages virus spread. Next, the review describes the current state of knowledge about spread of plant viruses at the critical agro‐ecological interface between managed and natural vegetation. There is an urgent need to understand how viruses move in both directions between the two and be able to anticipate these kinds of events. To obtain an understanding of, and ability to foresee, such events will require a major research effort into the future. The review finishes by discussing the implications of climate change and rapid technological innovation for the types of research needed to avoid virus threats to future world food supplies and plant biodiversity. There has been lamentably little focus on research to determine the magnitude of the threat from diseases caused in diverse plant virus pathosystems under different climate change scenarios. Increasing technological innovation offers many opportunities to help ensure this situation is addressed, and provide plant virus ecology and epidemiology with a very exciting future.